Use of a Nutrition Behavior Change Counseling Tool: Lessons from a Rapid Qualitative Assessment in Eastern Zambia - Weiss, Ingrid; Stepanovic, Serena; Chinyemba, Ulembe; Bateman, Jessica; Hemminger, Carolyn; Burrows, Emily (Frontiers in Public Health, 2016)
The U.S. Agency for International Development Feed the Future Mawa Project – led by Catholic Relief Services – aims to improve food and economic security for farming households in Zambia’s Eastern Province. Mawa employs social and behavior change (SBC) strategies with households and communities to improve nutrition and reduce stunting among children under two (CU2). To support these strategies, sub-partner University Research Co., LLC employed a participatory process to develop a series of 35 action cards, each illustrating one project-promoted behavior, that are used at household and community group levels. Caregivers of CU2 are given a full set of action cards to promote household dialogue and support for the promoted behaviors. As a final step in the action card tool development process, a qualitative rapid assessment was conducted 1 month after implementation to investigate preliminary ways action cards were being used, and if the methods of using the cards had the potential to impact behavior change. The research team conducted nine key informant interviews and four focus group discussions with Mawa staff and administered 41 qualitative interview questionnaires with project participants in the Chipata and Lundazi districts. Although not based on a representative sampling frame, the assessment produced valuable results for program improvement purposes. It also provided a feedback mechanism for community-based staff and project participants, a crucial step in the participatory tool development process. The assessment found that Mawa staff at every level use action cards combined with at least one other social behavior change tool for each nutrition intervention. Our results suggest that Mawa staff and project participants share a common understanding of the cards’ purpose. Each group noted that the cards provide a visual cue for action and reinforce previous Mawa nutrition messages. Intended uses confirmed by the assessment include encouraging household cooperation, negotiating behavior change, telling stories, and integrating messages with other project sectors. Based on the findings, recommendations for future project activities include aligning efforts against a theory of change to optimize use of all SBC tools; leveraging action card use to strengthen cross-sectoral integration within Mawa; and specific ongoing monitoring of action card use to improve activity implementation.